2016
DOI: 10.1097/id.0000000000000412
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Retrospective Evaluation of Dental Implants Placed in Resorbed Jaws Reconstructed With Appositional Fresh-Frozen Bone Allografts

Abstract: Implant loss was strictly related to the lack of primary osseointegration. Female sex and old age were found to be risk factors, which could negatively influence implant survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…The authors concluded that FFB is a reliable grafting material for restoring the mandibular alveolar ridge for the insertion of dental implants. Also, in a more recent retrospective study, Maiorana et al [27] evaluated 262 implants, placed in the resorbed jaws of 45 patients following reconstruction with appositional FFB from femoral head or iliac crest allografts. The survival rate, irrespective of the anatomical position of the implants, was 90.84% over a mean follow-up period of 50 months.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that FFB is a reliable grafting material for restoring the mandibular alveolar ridge for the insertion of dental implants. Also, in a more recent retrospective study, Maiorana et al [27] evaluated 262 implants, placed in the resorbed jaws of 45 patients following reconstruction with appositional FFB from femoral head or iliac crest allografts. The survival rate, irrespective of the anatomical position of the implants, was 90.84% over a mean follow-up period of 50 months.…”
Section: Discussionmentioning
confidence: 99%
“…Ridge augmentation and guided bone regeneration procedures may be too invasive in older adults and the results are generally unsatisfactory [28]. A long term retrospective study by Maiorana and co-workers have identified old age as one of the risk factors which negatively influenced implant survival in cases where dental implants were placed in resorbed jaws augmented using appositional bone allografts [31]. Instead Schimmel et al have suggested the use of ultra-wide 6 mm implants in cases of severe ridge resorption.…”
Section: Periodontal Therapy and Implant Prosthodonticsmentioning
confidence: 99%
“…Given that failure is an important occurrence in dental implants, several papers have been published where this problem has been treated from different points of view such as clinical studies and finite element analysis [ 10 14 ]. However, most of these studies have been done from a deterministic point of view.…”
Section: Introductionmentioning
confidence: 99%